Legislative policy-making authority, party system size, and party system nationalization. (June 2017) - Hicken, Allen; Stoll, Heather
Abstract: How does the internal organization of legislatures shape the legislative party system? We argue that the size and nationalization of the national legislative party system is related to the size of the legislative prize—namely, to how the legislature's internal rules and structures concentrate policy-making authority in the hands of the largest party. To test this argument, we draw on studies of legislative organization to develop a measure of the concentration of legislative policy-making authority. Using two time series cross sectional data sets of post-war elections, one of advanced industrial democracies with pure parliamentary systems and one of all advanced industrial democracies, we find support for our argument and note that the effect of internal legislative structures is larger than that of the electoral system. We also show that the incentives to aggregate and consolidate the legislative party system are generally stronger where there are few external constraints on the legislature.